Pregnancy in an unicorne uterus nocommunicating rudimentary horn - Shimajuko, Ricardo (2015)
We describe a case of 20-week pregnancy in an unicornuate uterus noncommunicating rudimentary horn evidenced by laparotomy and confirmed by anatomopathology study. The literature is reviewed.